AROMATERAPI CITRUS AURANTIUM MEMPENGARUHI KECEMASAN PERSALINAN KALA 1 FASE AKTIF - Dina Octa Via; Dainty Maternity; Yuli Yantina; Dewi Yuliasari (Program Studi Kebidanan Fakultas Kedokteran Universitas Malahayati, 2021)
Background: Anxiety is a disturbance in feelings characterized by feelings of fear or worry that are deep and ongoing. Anxiety is the most common female psychological response to childbirth. Aromatherapy is the use of scents with essential oils that promote a sense of calm and help reduce anxiety.The purpose of this study was to determine the effect of Citrus aurantium aromatherapy on the level of anxiety during the first stage of active labor at RSIA Puri Betik Hati, Bandar Lampung City.Method: This type of research is quantitative, with a Quasi Experiment Design research design using a Two Group Pre–Post Test Design. The sampling technique used is Non Probability Sampling with Accidental Sampling technique. This study used 60 research samples, divided into 2 groups, namely 30 mothers in the intervention group and 30 mothers in the control group. Measurement of anxiety levels using the Hamilton Anxiety Rating Scale (HAM-A) measuring instrument, where data collection uses observation sheets and SOPs. Analysis of the data used is the Independent Sample T-Test.Results: From the results of the research conducted by the authors, it is known that the average value of the level of labor anxiety in the intervention/experiment group (Citrus aurantia Aromatherapy) was 14.93, while in the control group the average level of labor anxiety was 28.63 the significance value is 0.000, P value (0.05) means